Reading the Past: Cuneiform - Walker, Christopher B. F. (1987)
Origin and Development - Tablets and Monuments - Scribes and Libraries - The Geographical Spread - Decipherment - Sample Texts - Fakes - Where to See Cuneiform Inscriptions